African Youth Language: New Media, Performance Arts and Sociolinguistic Development Ellen Hurst-Harosh and Fridah Kanana Erastus (eds) (2019) - Boluwaduro, Stephen Olabanji (Sociolinguistic Studies, 2021)
African Youth Language: New Media, Performance Arts and Sociolinguistic Development Ellen Hurst-Harosh and Fridah Kanana Erastus (eds) (2019) Cham: Palgrave Macmillan ISBN: 978-3-319-64561-2 (hbk) ISBN: 978-3-319-64562-9 (e-book). Pp. 249